Evolution of Olfactory Receptors Tuned to Mustard Oils in Herbivorous Drosophilidae. (28th December 2021) - Matsunaga, Teruyuki; Reisenman, Carolina E; Goldman-Huertas, Benjamin; Brand, Philipp; Miao, Kevin; Suzuki, Hiromu C; Verster, Kirsten I; Ramírez, Santiago R; Whiteman, Noah K
Abstract: The diversity of herbivorous insects is attributed to their propensity to specialize on toxic plants. In an evolutionary twist, toxins betray the identity of their bearers when herbivores coopt them as cues for host-plant finding, but the evolutionary mechanisms underlying this phenomenon are poorly understood. We focused on Scaptomyza flava, an herbivorous drosophilid specialized on isothiocyanate (ITC)-producing (Brassicales) plants, and identified Or67b paralogs that were triplicated as mustard-specific herbivory evolved. Using in vivo heterologous systems for the expression of olfactory receptors, we found that S. flava Or67bs, but not the homologs from microbe-feeding relatives, responded selectively to ITCs, each paralog detecting different ITC subsets. Consistent with this, S. flava was attracted to ITCs, as was Drosophila melanogaster expressing S. flava Or67b3 in the homologous Or67b olfactory circuit. ITCs were likely coopted as olfactory attractants through gene duplication and functional specialization (neofunctionalization and subfunctionalization) in S. flava, a recently derived herbivore.